2014
DOI: 10.1155/2014/925485
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and Restoration of Hearing Loss Associated with the Use of Cisplatin

Abstract: Background. Cisplatin is a well known platinum-based chemotherapeutic agent used for the treatment of various malignant tumours. A frequent side effect of cisplatin therapy is ototoxicity. Unfortunately, currently there are no available treatments. Material and Methods. Experimental, clinical studies and reviews published between 2004 and 2014 in the English medical literature concerning ototoxicity were selected using Medline, PubMed, and Google Scholar databases. Inclusion criteria were cisplatin-induced oto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 40 publications
1
49
1
3
Order By: Relevance
“…The cytokines involved in the lesion induced by cisplatin, such as TNF-α, IL-1, and iNOS, are affected by preconditioning, indicating a possible mode of action of RIPC. The decreased generation of ROS by RIPC can explain the decrease in cisplatin-induced cell damage in the DNA damage-independent pathway, and the main mechanism of action may be a decrease in oxidative stress [10]. We evaluated the BSAEP because this evaluation is easy to perform and has less variability and greater reproducibility than assessment of distortion product otoacoustic emissions [44], though many studies still use the latter method [45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cytokines involved in the lesion induced by cisplatin, such as TNF-α, IL-1, and iNOS, are affected by preconditioning, indicating a possible mode of action of RIPC. The decreased generation of ROS by RIPC can explain the decrease in cisplatin-induced cell damage in the DNA damage-independent pathway, and the main mechanism of action may be a decrease in oxidative stress [10]. We evaluated the BSAEP because this evaluation is easy to perform and has less variability and greater reproducibility than assessment of distortion product otoacoustic emissions [44], though many studies still use the latter method [45].…”
Section: Discussionmentioning
confidence: 99%
“…The protection against the ototoxic effects of cisplatin by RIPC in mice is related to the modulation of these cytokines, as shown in other organs [35]. Moreover, the production of ROS is essential in cisplatin-induced lesions [10] and is most likely decreased by RIPC, as demonstrated in other organs [46]. The effect of RIPC on cisplatin-induced ototoxicity in rats also depends on the modulation of other cytokines, such as iNOS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is used clinically for head and neck, lung, bladder, cervical, ovarian, testicular, and gastrointestinal cancers as well as childhood cancers such as neuroblastoma and medulloblastoma [ 14 ]. One of its major side effects is irreversible sensorineural hearing loss that occurs with an average incidence of 62 % of patients treated with cisplatin [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent strategies to avoid the ototoxic effect of cisplatin are mostly about ROS (Deavall et al 2012). Numerous studies have been conducted on prevention and restoration of the ototoxicity related to cisplatin (Chirtes & Albu 2014;Harrison et al 2015). These studies have suggested that antioxidants prevent ototoxicity.…”
Section: Introductionmentioning
confidence: 99%